Production and Application of Biosensors: A Brief Review (Research, Society and Development, 2018)
In a modern world where efficiency, precision and time savings have been prioritized, a new frontier has been seen in the biosensors to be explored. A potential alternative to the current means of quantification and qualification, the biosensors have been gaining more and more prominence as they are devices of quantification and qualification cheaper and simple, when compared with the current techniques and with the advantage of being able to be used many times in the place where the sample is collected. According to its application is produced by different methods, in which it has in its basic constitution a sensor element of biological origin, an inorganic half-conductor used as a transducer and a signal processing device. In this article we show the scientific production involving biosensors, together with their synthesis method, which differs according to their application in order to detect the most varied analytes, chemical species and even living organisms.